PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP PEMAHAMAN KONSEP BELAJAR PPKN SISWA SEKOLAH DASAR - Sholehuddin, Sholehuddin; Fiolanisa, Sasa (Elementar : Jurnal Pendidikan Dasar, 2024)
This research is motivated by problems in Civics subjects which are considered boring and difficult because they are theoretical and rote. Apart from that, in the learning process teachers only teach with lectures without using innovative learning models and do not encourage students to think critically. So students don't understand the concept and are only concerned with the results rather than the process. This causes understanding of concepts in PPKn to be low and less meaningful. The purpose of this research is to determine the influence and measure the magnitude of the influence of using the RADEC learning model on understanding the concept of Civics in class V of SD Negeri Ciputat 06. This research is a quantitative research using a quasi-experimental method. The sampling technique in this research used purposive sampling. The sample for this research was 30 students in class 5A and 30 students in class 5B. Data collection used test techniques in the form of essay questions totaling 10 pretest questions and 10 posttest questions. The results of the research show that there is a significant influence on the test results between the experimental class and the control class, as evidenced by the results of independent sample t test calculations with sig (2-tailed) 0.00 <0.05 and tcount 10.059 > ttable 2.0017, so Ho is rejected and Ha accepted. The magnitude of this influence is 2.32. This is proven by the results of the effect size test calculation using the Cohen's d formula and large categories. So, it can be concluded that the use of the RADEC learning model has an influence on students' understanding of Civics learning concepts with a large influence of 2.32 in the large category. This learning model can be an effective and interesting alternative to increase students' understanding of the material and interest in learning.